Exploring Student Experiences Knowledge Communication to Canva Mobile Interface : A Qualitative Study on Second Semester Students of Boyolali University - Muhammad Zidan Syahrio; Fanny Hendro Aryo Putro; Topan Setiawan; Sri Hartini; Wahyuning Chumaeson (Jurnal Penelitian Pendidikan IPA, 2025)
The development of digital technology has changed the way students interact with learning media, including in the creation of visual content. One of the most widely used applications among students is Canva Mobile, which offers convenience in designing various academic needs practically through mobile devices. This research aims to explore the experiences of second-semester students of the Communication Science Study Program at the University of Boyolali in using the Canva Mobile interface as a supporting medium for completing academic assignments. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews and observation. Informants were selected using purposive sampling, followed by snowball sampling. The collected data were analyzed through data reduction, data presentation, and conclusion drawing. The results show that the majority of students feel comfortable and find it easy to use Canva Mobile. Its user-friendly interface, diverse features, and flexible access are the main reasons for its popularity. Canva Mobile has been proven to improve the quality of students' visual assignments and support creativity development in the field of visual communication. However, there are some obstacles, such as the limited features in the mobile version compared to the desktop version, as well as restricted access to premium elements. This study concludes that Canva Mobile is an effective, adaptive, and relevant learning medium that aligns with the needs of today’s digital-native students. Students' positive experiences in using this application serve as evidence that mobile technology can be optimally integrated into higher education.